2019
DOI: 10.1109/access.2019.2897691
|View full text |Cite
|
Sign up to set email alerts
|

Low-Light Underwater Image Enhancement for Deep-Sea Tripod

Abstract: To monitor the sedimentary process and morphological evolution in the South China Sea, free-ascending deep-sea tripod (FDT) has been developed. This FDT was equipped with a deep-sea camera and landed on the sea floor at a depth of 2100 m. Although the FDT was equipped with an artificial light, the battery capacity limited the duration and intensity of light. Therefore, enhancing such low-illumination images to obtain clear visual effects is an important advancement for analyzing the geological evolution proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Li Y et al proposed an adaptive bright-color channel-based low-light image-enhancement method to enhance the underwater images. The experimental results demonstrated that the proposed method was effective [19]. Lu H et al proposed a light field imaging approach for solving underwater imaging problems in a low-intensity light environment.…”
Section: Introductionmentioning
confidence: 89%
“…Li Y et al proposed an adaptive bright-color channel-based low-light image-enhancement method to enhance the underwater images. The experimental results demonstrated that the proposed method was effective [19]. Lu H et al proposed a light field imaging approach for solving underwater imaging problems in a low-intensity light environment.…”
Section: Introductionmentioning
confidence: 89%
“…Since the information of red channel is not dependable in diverse underwater scenes based on the analysis of UDCP [22], the maximum intensity prior (MIP) [23] and blurriness-based [24] approaches are proposed. To dealing with the lowlight deep-sea circumstance, Li [25] proposes an adaptive bright-color channel based low-light underwater enhancement method followed by a denoising and a color correction method to enhance such images and remove noise and artifacts. In [10], Yang et al combine maximum scene depth estimation and adaptive color correction to accurately estimate the background light.…”
Section: Underwater Image Restoration Methodsmentioning
confidence: 99%
“…Edwin Land composed the Retinex Theory. [10][11][12] The word 'Retinex' was derived from two words -Retina + Cortex. This theory states that the way we perceive the colours of the objects around us results from the light incident around it and the wavelength of light that the object reflects, which enters our eyes.…”
Section: Retinex Theorymentioning
confidence: 99%